Genetic and structural validation of phosphomannomutase as a cell wall target in Aspergillus fumigatus. Issue 1 (1st March 2021) - Zhang, Yuanwei; Fang, Wenxia; Raimi, Olawale G.; Lockhart, Deborah E. A.; Ferenbach, Andrew T.; Lu, Ling; van Aalten, Daan M. F.
Abstract: Aspergillus fumigatus is an opportunistic mold responsible for severe life‐threatening fungal infections in immunocompromised patients. The cell wall, an essential structure composed of glucan, chitin, and galactomannan, is considered to be a target for the development of antifungal drugs. The nucleotide sugar donor GDP‐mannose (GDP‐Man) is required for the biosynthesis of galactomannan, glycosylphosphatidylinositol (GPI) anchors, glycolipid, and protein glycosylation. Starting from fructose‐6‐phosphate, GDP‐Man is produced by the sequential action of the enzymes phosphomannose isomerase, phosphomannomutase (Pmm), and GDP‐mannose pyrophosphorylase. Here, using heterokaryon rescue and gene knockdown approaches we demonstrate that the phosphomannomutase encoding gene in A. fumigatus ( pmmA ) is essential for survival. Reduced expression of pmmA is associated with significant morphological defects including retarded germination, growth, reduced conidiation, and abnormal polarity. Moreover, the knockdown strain exhibited an altered cell wall organization and sensitivity toward cell wall perturbing agents. By solving the first crystal structure of A. fumigatus phosphomannomutase ( Af PmmA) we identified non‐conservative substitutions near the active site when compared to the human orthologues. Taken together, this work provides a genetic and structural foundation for the exploitation of Af PmmA as a potential antifungal target. Abstract :